Pola Pengelolaan Yang Efektif Pada Objek Wisata Pantai Carocok Dalam Meningkatkan Pendapatan Masyarakat Sekitar Objek Wisata - Azizah, Siti Nur; Irianto, Agus (Jurnal Salingka Nagari, 2024)
This study aims to determine how to apply an effective management pattern at the Carocok Beach tourist attraction. This research method is qualitative with the type of field research. Research informants were determined using the snowball sampling technique. Data collection with interview, observation, and documentation techniques. Analysis of the data using the Miles and Huberman analysis. The results of study show the management of the Carocok Beach tourist attraction has been carried out well and can increase the income of the surrounding community, but not optimal. This can be seen from the problems that occur in the Carocok Beach. Such as lack of cleanliness, illegal levies, traders not well organized and the price of goods is relatively expensive. For this reason, an effective management pattern is needed at Carocok Beach. The ways that can be done are (1) improving the arrangement of the Carocok Beach, (2) making entrances and exits of tourist objects, (3) making a schedule of tourist visits, (4) completing supporting facilities for the tourism activities, (5) improving performance security guards, (6) conducting tourism awareness trainings, (7) involving relevant agencies in the management.